Pharmacological and epidemiological studies on the drug-sensitivity of trypanosomes isolated from a peri-urban dairy production system in Uganda. - Olila, D. (University of Nairobi, 1999)
The understanding of factors contributing to the appearance and maintenance of trypanosome drug resistance in the field is very limited,. yet this type of information would be very useful in the design of trypanosomosis control strategies. This thesis describes a study that was carried out in Mukono County, a peri-urban dairy production system near Kampala (Uganda). It had the following main objectives: a) to characterise the drug-sensitivity phenotype(s) of trypanosome field isolates collected between 1995 and 1996 from cattle; b) to determine the species and subspecies of trypanosome populations and their prevalence over the same period in cattle; c) to evaluate an isometamidium-enzyme-linked immunosorbent assay (ISMM-ELISA) using sera and use the resulting data to monitor the use of isometamidium and as a tool to indirectly assay for drug resistance; d) to establish whether the trypanosome isolates from cattle might be of zoonotic importance; and e) to analyse the factors associated with trypanocide usage and efficacy. In the first part of this study, 486 cattle from 50 farms in Mukono County were monitored for trypanosome infections over a two-year period (1995 to 1996). Eighteen trypanosome isolates were characterised in vivo for their sensitivity to isometamidium (ISMM), diminazene (DIM) and homidium (HOM). Ten of the isolates were from animals that had the highest serum ISMM concentrations (ranging from 0.3-4.5ng/ml). as determined by the ISMM-ELISA. All 18 isolates exhibited low pathogenicity in cattle and were sensitive to DIM at 3.5-mg/kg-body weight (BW) and ISMM at 0.5 mg/kg BW. In goats, two of the isolates were highly pathogenic, producing CNS involvement. All eight populations examined in goats were sensitive to DIM at 3.5 mg.kg BYV.However. two populations relapsed after treatment with ISMM at 0.5mg/kg BW. and four relapsed after treatment with HOM at 1.0 mg/kg BW. In mice. the 50% curative dose (CD50) values for the populations ranged from OJ to 1.9 mg/kg BW for DIM. from 0.02 to 0.10 rng/kg BW for ISMM and from 0.9 to 3.8 mg/kg BW for HOM. Thus. by comparison to reference drug-sensitive populations. all the isolates were highly sensitive to DIM and ISMM even though some expressed moderate levels of resistance to HOM. All the isolates contained only T brucei and/or T vivax. Twenty five percent of the T brucei populations studied were human serum resistant, indicating that cattle might be reservoir hosts for the causative agent of human sleeping sickness in this area. In the second part of this study, an improved methodology for a competitive enzyme immunoassay (CEIA) for ISMM was developed. The equilibrium method was modified to a sequential saturation procedure, because of unacceptably high intersample variation in the former. For instance. in the equilibrium procedure, the optical densities (ODs) ranged from 0.208 to 3.332, with a very high coefficient of variation (CV) of 94.8%, in adult cattle. Using the sequential saturation procedure, the CV for sera from 20 untreated cattle was 6 %. Four-parameter logistic calibration curves obtained using the sequential saturation method showed the concentration of isometamidium required for 50% competition to be approximately 1.0 ng/ml; half that previously reported for the equilibrium method. This shift in the calibration curve, together with the reduction in the inter-sample variance for untreated cattle. resulted in an improved lower limit of detection of the order of 0.1-0.2 ng/m!. In the third part of the study. the newlv developed ISl\lM-ELISA (sequential saturation) was used to monitor ISMM concentrations in sera from Mukono cattle. after block treatment with ISMM (Samorin": 1.0 mg/kg BW). Serum samples obtained from 474 cattle. distributed among 50 farms were analysed. For each animaL determinations were available for samples collected from up to four occasions. these being day 0 (the day of ISMM block-treatment) and three. approximately monthly, occasions thereafter. The mean serum ISMM concentrations were: at day zero (before drug administration). 0.67±1.28 ng/ml; at 30 days post-treatment (OPT), 0.67±0.60 ng/ml; at 60 OPT, 0.22±0.27 ng/ml; and by 90 OPT, below the detection limit of the assay. Mixed logistic regression analysis of mean serum concentrations for the 3 breed categories (exotics. locals and crosses) at 30, 60 and 90 OPT, revealed a higher probability of detecting ISMM in local than exotic cattle at all time points; suggesting a possible breed effect on the pharmacokinetics of isometamidium. Finally, factors affecting trypanocidal drug use and efficacy in Mukono were also examined. There were no obvious factors associated with drug use in the study area. Of the 1847 ISMM treatments given during the study, 234 infected cases (failures) were diagnosed during the post-treatment observation period. Of the 234 (failures), only 30 (7.4%) occurred between 7-90 days post-treatment, indicating the high efficacy of ISMM. In conciusion. the findings in this study provide important information in deciding the best control option for trypanosornosis in Mukono County. It is suggested that an integrated disease management strategy may be the best approach for the study area.